The Industry 5.0 Concept as a Game Changer for the Fourth Industry Revolution - Saniuk, Sebastian; Grabowska, Sandra (Koncepcja Przemysłu 5.0 jako game changer dla czwartej rewolucji przemysłowej, 2023)
The concept of Industry 5.0 is a game changer for the fourth industrial revolution. It extends the ideas of Industry 4.0 with values related to sustainable development, human focus and resilience of the industry. The purpose of the chapter is to identify the critical areas of digital technologies used during the fourth industrial revolution and to identify their impact on achieving the main goals of Industry 5.0, i.e., human orientation, sustainable development and resistance to all kinds of interference. The authors used the method of critical analysis of the literature and conducted an expert survey of selected experts representing the business and academic communities. In addition, the chapter draws attention to the increase in competency requirements of employees related to the implementation of Industry 5.0 technology areas.
Saniuk, S., and Grabowska, S. (2023). The Industry 5.0 Concept as a Game Changer for the Fourth Industry Revolution. In M. Hajdas (Ed.), Game Changers in Management (pp. 44-53). Publishing House of Wroclaw University of Economics and Business.
Keywords: Industry 5.0; human-centric; resilience; sustainability; competencies; Przemysł 5.0; orientacja człowieka; odporność; zrównoważony rozwój; kompetencje